Peer support systems with children with Autism Spectrum Disorders in inclusive schools. A systematic review - Liesa Orús, Marta; Latorre Cosculluela, Cecilia; Vázquez Toledo, Sandra (Revista Complutense de Educación, 2017)
As a result of inclusion-oriented policies, in recent years a growing interest in all children learn together in schools is detected. Concretizing for the population of children with Autism Spectrum Disorders, this approach has led a rejection of more individualized to let emerge an educational inclusive perspective, emphasizing the importance of peer influence with typical development (TD) in their social and communicative skills. The pedagogic use of peer support systems involves teaching a series of strategies and guidelines to children without difficulties in order to facilitate the social interaction of children wits ASD. In this way, in this systematic review it appears the systematic analysis of 11 empirical studies using support and peer assistance with children with ASD in inclusive school settings. After data extraction, certain differences are found in the type of training given to children with TD and in activities implemented with peers with ASD, depending on educational stage where they are and the place where the intervention is implemented. For both educational stages (elementary and primary), role-playing and modeling are the two most commonly adopted procedures to training peers who are going to implement later the peer support system with children with TEA. At the time of implementing these interventions, the type of activity par excellence used in the kindergarten stage, is the game, while more complex activities such as reinforcing communicative attempts and attracting attention, are introduced in primary.